Older adult pedestrian trauma: A systematic review, meta-analysis, and GRADE assessment of injury health outcomes from an aggregate study sample of 1 million pedestrians. (March 2021) - Rod, J.E.; Oviedo-Trespalacios, Oscar; Senserrick, Teresa; King, Mark
Highlights: Pedestrians aged 60+ have a higher risk of severe/fatal injury than pedestrians <60 when involved in pedestrian crashes or falls. Pedestrians aged 60+ are at higher risk of lung injuries, intracranial injury, and pelvis fractures than pedestrians <60. The overall quality of the body evidence evaluating older pedestrian trauma is low. There is a need of research evaluating injury health outcomes due to pedestrian falls. Abstract: This systematic review sought to assess older adult pedestrian injury severity, injury by anatomical location and incidence proportions, including comparisons to younger age groups when available and provide an analysis of the quality of the existing evidence. A structured search was conducted in PubMed, Embase, Scopus, CINAHL, PsycInfo, AMED, Web of Science, LILACS and TRID. STROBE was used to assess the reporting quality of the included studies. Random-effect model meta-analysis served to obtain pooled relative risk, incidence proportions and standardized mean differences for different outcomes due to pedestrian crashes comparing older and younger pedestrians, while meta-analyses could not be conducted for pedestrian falls. We screened 7460 records of which 60 studies (1, 012, 041 pedestrians) were included in the review. Injured pedestrians 60+ compared to those <60 were found to have a higher relative risk of severe injury (pooled relative risk RR 1.6, 95 % CI: 1.4–2.0 p < 0.001), critical care admission (pooled RR 1.5, 95 %CI: 1.3–1.8 p < 0.001), and fatality (pooled RR of 3.7, 95 % CI: 3.0–4.5 p < 0.001). Pedestrians 60+ also had higher incidence rates of pedestrian falls causing higher injury severity. GRADE was used to evaluate evidence quality, with the results suggesting that the overall quality of the evidence supporting these findings was low. Further research is needed to understand health risks associated with older pedestrian trauma and to develop effective risk management strategies.